Pengaruh Current Ratio dan Debt to Assets Ratio terhadap Kinerja Keuangan Perbankan Swasta Nasional yang Terdaftar di BEI Periode 2014-2023 - Amelia, Firly (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
When evaluating the financial success of a company, liquidity and solvency are crucial factors to consider. This research aims to analyze the influence of the Current Ratio and Debt to Assets Ratio on the Financial Performance of PT Bank Mestika Dharma Tbk., PT Bank Central Asia Tbk., and Bank Mega Tbk during the 2014-2023 period. The author utilize quantitative method using secondary data obtained from annual reports. The data analysis technique involves multiple linear regression, t-test, F-test, and coefficient of determination test using SPSSv22. The results from the t-test indicate that the Current Ratio does not have a significant effect on Financial Performance, and the Debt to Assets Ratio also does not have significantly affect Financial Performance. The F-test results show that both the Current Ratio and Debt to Assets Ratio do not have a significant effect on Financial Performance.